Description of Two Cases of Anaplastic Large Cell Lymphoma Associated with a Breast Implant. (27th June 2019) - Crèvecoeur, Julie; Jossa, Véronique; Somja, Joan; Parmentier, Jean-Claude; Nizet, Jean-Luc; Crèvecoeur, André
Abstract : Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is a recently recognized provisional entity in the 2017 revision of the World Health Organization classification of lymphoid neoplasms. Although the majority of the cases described in the literature demonstrate an effusion confined to the capsule of the breast implant, this rare pathology can also invade the capsule and adjacent tissues and/or involve lymph nodes. We hereby report two new cases of BIA-ALCL in a 58-year-old and a 47-year-old Caucasian female who received a silicone breast implant. The first patient showed a sudden and rapid right breast volume increase 6 years after the implantation surgery. As for the second patient, a left breast volume increase was observed also suddenly and quickly 11 years after surgery. In both cases, an uncompressed mammography was performed allowing a new approach to highlight periprosthetic fluid reaction. Pathologic examination of the fluid collection revealed atypical cells positive for CD30 and CD45 and negative for ALK and CK7. This allowed pathologists to diagnose a breast implant-associated anaplastic large cell lymphoma. Patients were treated with bilateral capsulectomy with no additional local or systemic therapy. The development of breast augmentation may come with an increase in the frequency of this pathology. Radiologists and senologists must therefore be careful when women with breast implants show an increase of breast volume and all cases of BIA-ALCL must be recorded and reported.